PENANGANAN BENCANA DAN TRANSFORMASI PENGETAHUAN TENTANG KEGEMPAAN DI INDONESIA PADA ERA KOLONIALISME: SEBUAH PAPARAN SEJARAH - Riskianingrum, Devi (Jurnal Sejarah dan Budaya, 2010)
Abstract: The idea of disaster have gone through three important phases, namely act of God, act of nature and acts of men and women. As well as other disaster, earthquake force society to account for the incomprehensible. Thus, learning from the historical experience can provide useful insights into the problems posed by the threat of earthquakes. By doing so, we learn and understand the way in which the colonial governmentâs response to the catastrophes. Additionally, it also explore that process of transforming the knowledge among the colonial goverments and the natives.